Les victimes de viol devant les tribunaux à la fin du Moyen Âge d’après les sources dijonnaises et lyonnaises - Gonthier, Nicole (Criminologie, 1994)
At the end of the Middle Ages, the manner in which the courts of justice punished rapists clearly shows how seriously such crimes were judged at that time. Endeavoring to increase their juristic power and worrying that the propagation of rape would corrupt the entire society and threaten its survival, impelled the judges and their officials —princes, bishops, and municipal bodies — to deal with all complaints and to initiate inquiries about them. A study of the progressive steps undertaken in the preliminary investigations of these cases reveals that after an inquiry into the accuser's reputation, the judges demanded numerous proofs from the victim about the rape. Moreover, a clinical examination was demanded from a midwife. Thus, in addition to the scientific proof and the witness's statements, the investigators were able to arrive at a better assessment of the rapist. The rapist, in turn, under the distressful solitude in his cell where he had been incarcerated by the police as soon as the complaint was made, finally admitted to the crime and renounced having degraded and defamed his accuser, ft was then up to the court to punish the offender. These offenders were treated severely, particularly if they had attacked moral and social values by deflowering children and virgins.